2020
DOI: 10.1080/13639080.2020.1722988
|View full text |Cite
|
Sign up to set email alerts
|

Economic returns to adult vocational qualifications

Abstract: Some countries have certifying institutions for competence acquired at the workplace. These institutions provide incentives for workplace training that may have favourable effects on productivity, earnings and labour market participation. We present evidence on the earnings effects of attaining vocational qualifications in adulthood through two alternative routes: (1) apprenticeship and (2) recognition and testing of vocational competence acquired through relevant work experience. Drawing on longitudinal admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Midtsundstad et al [10] has reviewed the impact of formal adult learning programs on employment sector and labour market participation and have found strong correlation of the basic skills imparted to them with their output efficacy. Bratsberg et al [17] has reported an imperative contribution of vocational uppersecondary education in averting unemployment risks with amended opportunities of re-employment for adult learners. Picchio et al [18]…”
Section: Platforms Required For Adult Education and Lifelong Learning...mentioning
confidence: 99%
“…Midtsundstad et al [10] has reviewed the impact of formal adult learning programs on employment sector and labour market participation and have found strong correlation of the basic skills imparted to them with their output efficacy. Bratsberg et al [17] has reported an imperative contribution of vocational uppersecondary education in averting unemployment risks with amended opportunities of re-employment for adult learners. Picchio et al [18]…”
Section: Platforms Required For Adult Education and Lifelong Learning...mentioning
confidence: 99%
“…VET emphasises the acquisition of technical skills and knowledge to foster behavioural competence in the workplace (Colley et al , 2003). The system encompasses where vocational skills are developed (training institution) and the degree of employer involvement (workplace) (Bratsberg et al , 2020). For most African countries, most of the labour market destinations are still in the urban informal or rural subsistence economies with very little literature present on this subject.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This did not happen, traditional apprenticeships survived and in 1994 the government began to fund 'modern apprenticeships'. Research quickly began to show that apprentice training boosted earnings to the same extent as university degrees, and indeed that the earnings of ex-apprentices overlapped with graduates' salaries (Bratsberg et al 2020;McIntosh 2007; Paton 2014; Sutton Trust 2014). 'Modern' was subsequently dropped from the title, and by 2015 the apprentice 'brand' was being applied to nearly all governmentsupported training.…”
Section: Apprenticeshipsmentioning
confidence: 99%